Crowdsourced innovation: How community managers affect crowd activities - Lars Hornuf; Sabrina Jeworrek (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2018)
In this study, we investigate whether and to what extent community managers in online collaborative communities can stimulate crowd activities through their engagement. Using a novel data set of 22 large online idea crowdsourcing campaigns, we find that active engagement of community managers positively affects crowd activities in an inverted U-shaped manner. Moreover, we evidence that intellectual stimulation by managers increases community participation, while individual consideration of users has no impact on user activities. Finally, the data reveal that community manager activities that require more effort, such as media file uploads instead of simple written comments, have a larger effect on crowd participation.
urn:nbn:de:gbv:3:2-96417
Keywords: J21; J22; L86; M21; M54; O31; 330; crowdsourcing; open innovation; crowdsourced innovation; crowdworking; ideation; managerial attention